Material aspects of letter writing in the Graeco-Roman world: 500 BC - AD 300 - Sarri, Antonia (Materiale Textkulturen, 2017)
Letter writing was widespread in the Graeco-Roman world, as indicated by the large number of surviving letters and their extensive coverage of all social categories. Despite a large amount of work that has been done on the topic of ancient epistolography, material and formatting conventions have remained underexplored, mainly due to the difficulty of accessing images of letters in the past. Thanks to the increasing availability of digital images and the appearance of more detailed and sophisticated editions, we are now in a position to study such aspects. This book examines the development of letter writing conventions from the archaic to Roman times, and is based on a wide corpus of letters that survive on their original material substrates. The bulk of the material is from Egypt, but the study takes account of comparative evidence from other regions of the Graeco-Roman world. Through analysis of developments in the use of letters, variations in formatting conventions, layout and authentication patterns according to the sociocultural background and communicational needs of writers, this book sheds light on changing trends in epistolary practice in Graeco-Roman society over a period of roughly eight hundred years. This book will appeal to scholars of Epistolography, Papyrology, Palaeography, Classics, Cultural History of the Graeco-Roman World
Open Access
Keywords: Verzeichnis; Papyrus; Brief; Griechisch; Geschichte 500 v. Chr.-300; Konvention; Ägypten